Children and adolescents with a chronic condition in the public school space – in search of an effective model of psychopedagogical support - Krauze-Sikorska, Hanna (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Hanna Krauze-Sikorska, Children and adolescents with a chronic condition in the public school space – in search of an effective model of psy-chopedagogical support. Interdisciplinary Contexts of Special Pedagogy, no. 26, Poznań 2019. Pp. 205–318. Adam Mickiewicz University Press. ISSN 2300-391X. e-ISSN 2658-283X. DOI:https://doi.org/10.14746/ikps.2019.26.14 Chronic condition may, in time, become a specific kind of „stigma” that determines the formation of a specific “conveyor belt” which determines the trajectories of the fate of children and adolescents. Analysing the functioning of children and adolescents with a chronic condition, for which the school should provide (as for other students) the conditions of learning, both in the cognitive and in the directional aspects, one may indicate not only the imperfections of educational activities, but also a myth of noble ideas inscribed in the function of school, as a place of universal development of every student. The article is a proposal of employing, within the process of educating children and adolescents with a chronic condition, an eclectic model of activities, based on their complexity and sequentiality. The model refers to models proposed by Frederick C. Thorne, or Richard James, used in situations of crisis intervention: the equilibrium model, the cognitive model, and the social change model.